Factors related to nurses’ knowledge and attitudes towards pain management: a cross-sectional study of 32 tertiary hospitals in Anhui province, China - Yidan Zhang; Jiadong Wang; Shumin Bi; Shangui Chen; Zhaowen Peng; Zhiju Li; Chunxia Ren (BMJ Open)
Objective Recognising and managing pain was considered an essential clinical skill for nurses. This study aimed to assess nurses’ knowledge of pain management and the factors associated with it.Design A cross-sectional survey was conducted in Anhui province, China, using the Knowledge and Attitudes Survey Regarding Pain (KASRP) (2014). Multiple linear regression analysis identified factors associated with nurses’ KASRP Scores.Setting The study was carried out in 32 tertiary hospitals in Anhui province, China, from 21 May to 13 July 2023.Participants 6928 registered nurses.Outcome measures The main outcome was the KASRP Score, reflecting nurses’ knowledge and attitudes towards pain management. We assessed the associations between sociodemographic factors, knowledge-sharing behaviours (KSBs) and KASRP Scores.Results Among the 6928 nurses analysed, the average KASRP Score was 17.70±3.57, corresponding to a correct response rate of 44.55%. Gender (p=0.003), professional title (p<0.001), education level (p<0.001), hospital grade (p=0.002), work department (p<0.001), pain resource nurse status (p<0.001), receipt of pain training (p<0.001), level of concern for patient pain (p<0.001), and KSBS Score (p<0.001) significantly influenced knowledge and attitudes. XGBoost regression further identified pain training, clinical department and KSB as top predictors, with relative importance weights of 0.237, 0.170 and 0.135, respectively (R² = 0.268, MSE=38.3).Conclusions This large-scale study revealed inadequate knowledge and attitudes regarding pain management among nurses in Anhui province, with outcome scores associated with various demographic and professional factors. These findings highlighted the need for continuous education, enhanced academic training and supportive institutional policies. Nursing leaders should implement targeted training initiatives and promote knowledge-sharing environments to strengthen pain management competencies among nurses.